ISLAMIC WEALTH MANAGEMENT: HARMONIZING SPIRITUALITY AND FINANCIAL SUSTAINABILITY - T. Rizkan Polem; Sugianto; Marliyah (RADJA PUBLIKA, 2025)
Islamic wealth management represents a unique integration of ethical finance and spirituality, addressing the growing need for financial systems that prioritize sustainability and social justice. This study aims to explore how Islamic wealth management harmonizes spiritual principles and financial sustainability, focusing on emerging trends, challenges, and opportunities in the global context. The research employs a qualitative approach, utilizing case studies and literature reviews to analyze contemporary practices, theories, and applications. Data is drawn from scholarly articles, industry reports, and primary sources that examine Shariah-compliant wealth management practices, including zakah, waqf, and ESG integration. The findings highlight that Islamic wealth management frameworks ensure financial stability through risk-sharing mechanisms, enhance social welfare via ethical investments, and address global sustainability goals through the adoption of fintech innovations. Key challenges identified include the standardization of Shariah compliance, the need for gender inclusivity, and the alignment of ESG metrics with Islamic principles. These results imply that Islamic wealth management holds significant potential to contribute to a more equitable and sustainable global financial system.